Clinical profile of hypertension patients in primary health Care in Cirebon Regency, Indonesia - Tiar Masykuroh Pratamawati; Ahmad Fariz Malvi Zamzam Zein; Uswatun Khasanah; Donny Nauphar; Vincentius S.W. Budhyanto; Idrus Alwi; Asmarinah (Endocrine and Metabolic Science)
Introduction: Hypertension is a catastrophic non-communicable disease increasing in prevalence globally. This study aimed to assess the clinical profile of hypertensive patients in primary health care services in Cirebon Regency, Indonesia. Method: This descriptive study employed a purposive sampling method, recruiting 97 adult patients diagnosed with essential hypertension at the Talun Community Health Center, Cirebon Regency, West Java, from November 2023 to February 2024. Patients with secondary hypertension or hypertension in pregnancy were excluded. Data were collected through questionnaires, blood pressure measurements, and analysis of blood and urine samples. The clinical profile included family history, control status of hypertension, lifestyle factors, cardiometabolic parameters, and mental health status. Lifestyle factors encompassed both dietary habits and physical activity levels. Cardiometabolic parameters included body mass index (BMI), HbA1c, lipid profile, kidney function, and electrocardiogram. Mental health status was measured using the Depression Anxiety Stress Scales (DAAS). Univariate analysis was stated in frequencies, mean, or median. Results: The mean age of the participants was 51.33 (±1.07) years, predominantly female (84.54 %). Subjects with a family history of hypertension were 52.58 %, and 75.3 % had uncontrolled blood pressure. Most subjects (79.17 %) engaged in light daily physical activity, while only 4.2 % reported excessive sodium intake. The average BMI was 26.04 kg/m2, with 35.5 % classified as class 1 obese. Additionally, 12.4 % of subjects had diabetes mellitus, 41.2 % were prediabetic, and 80.41 % had dyslipidemia. Albuminuria was detected in 54.6 % of participants, and 7.2 % showed evidence of left ventricular hypertrophy. Regarding mental health, 37.50 % experienced anxiety, 8.33 % reported stress, and 4.17 % suffered from depression. Conclusion: The findings indicate a significant proportion of hypertensive patients in primary health care in Cirebon Regency have uncontrolled blood pressure. Sedentary lifestyle, obesity, dyslipidemia, albuminuria, and prediabetes were prevalent among these patients. Moreover, anxiety affected more than a third of the studied subjects, highlighting the need for comprehensive management strategies for managing hypertensive patients.